2007
DOI: 10.1002/ppul.20597
|View full text |Cite
|
Sign up to set email alerts
|

Human metapneumovirus bronchiolitis in infancy is an important risk factor for asthma at age 5

Abstract: hMPV-bronchiolitis in infancy was strongly associated with asthma as well as other forms of bronchial obstructive disease at third and fifth year of life. This association is, at least, as strong as the association observed with RSV infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
93
2
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(101 citation statements)
references
References 46 publications
0
93
2
6
Order By: Relevance
“…The strong association between hMPV infection and asthma in both children (Garcia-Garcia et al, 2007;Peiris et al, 2003) and adults (Williams et al, 2005), and the ability of hMPV infection to exacerbate hRSV disease (Bosis et al, 2005;Semple et al, 2005), illustrate the need to improve our understanding of hMPV-induced T-cell immunity, particularly as a prelude to therapeutic intervention. As hMPV can establish productive infection in the upper and lower respiratory tract (Alvarez et al, 2004;Hamelin et al, 2005;van den Hoogen et al, 2001), hMPV-expressed proteins have the potential to function as targets of CD8 + CTL responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The strong association between hMPV infection and asthma in both children (Garcia-Garcia et al, 2007;Peiris et al, 2003) and adults (Williams et al, 2005), and the ability of hMPV infection to exacerbate hRSV disease (Bosis et al, 2005;Semple et al, 2005), illustrate the need to improve our understanding of hMPV-induced T-cell immunity, particularly as a prelude to therapeutic intervention. As hMPV can establish productive infection in the upper and lower respiratory tract (Alvarez et al, 2004;Hamelin et al, 2005;van den Hoogen et al, 2001), hMPV-expressed proteins have the potential to function as targets of CD8 + CTL responses.…”
Section: Discussionmentioning
confidence: 99%
“…Young children, the elderly and immunocompromised individuals are particularly susceptible to hMPV-associated disease, emphasizing the need to understand the role of antiviral immunity in the control of infection. Several studies have indicated a strong association between hMPV disease and asthma in both children (Garcia-Garcia et al, 2007;Peiris et al, 2003;Tauro et al, 2008) and adults (Williams et al, 2005), implicating hMPV in ongoing or long-term adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…Measurements of cytokines implicated in asthma pathogenesis in nasal washes of HMPV-infected infants have yielded conflicting results (119,133). One retrospective study found a strong association between HMPV infection during infancy and the subsequent diagnosis of asthma (86). A major challenge for studies of respiratory viruses and asthma is the difficulty in firmly establishing a diagnosis of asthma during infancy, when acute wheezing associated with viral infections is common.…”
Section: Symptoms and Pathologymentioning
confidence: 99%
“…Previously, RSV and human metapneumovirus (HMPV) have been implicated as major aetiological agents for LRI [7,8], but human rhinoviruses (HRVs) are gaining recognition as significant LRI pathogens [9][10][11][12][13]. Infants hospitalised for HRV-induced wheezing in infancy were found to have increased risk of asthma at 6 yrs in one of the first studies to report HRVs as inducers of early childhood wheezing [9].…”
mentioning
confidence: 99%